PERUMUSAN MANAJEMEN STRATEGI PEMBERDAYAAN ZAKAT - Siti Aminah Chaniago (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
Strategymanagement is art and science of strategy formulation, implementation, and evaluation of decisions that enable organizations to reach their goals, focus on the process of goal-setting organization, develope policies and plans to achieve the objectives, and allocate resources to implement the policies and plan for the achievement of organization goals.Often there are obstacles in the management. This is due to many factors which are not integrated the management of each party contained in the management of tithe. If the principles and objectives of management held by amil zakatare implemented using modern management while applying the standard functions of management, the target seems to charity will be achieved.